2021
DOI: 10.1021/acs.jpcb.1c06498
|View full text |Cite
|
Sign up to set email alerts
|

Spin–Orbit Charge-Transfer Intersystem Crossing of Compact Naphthalenediimide-Carbazole Electron-Donor–Acceptor Triads

Abstract: Compact electron donor−acceptor triads based on carbazole (Cz) and naphthalenediimide (NDI) were prepared to study the spin−orbit charge-transfer intersystem crossing (SOCT-ISC). By variation of the molecular conformation and electron-donating ability of the carbazole moieties, the electronic coupling between the two units was tuned, and as a result charge-transfer (CT) absorption bands with different magnitudes were observed (ε = 4000−18 000 M −1 cm −1 ). Interestingly, the triads with NDI attached at the 3-C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 101 publications
1
28
0
Order By: Relevance
“…The scope of the reaction was assessed (Scheme 3) using a range of diaryl and aryl/alkyl secondary amines to yield 4 a – 4 d in the solid state (Figure 5). These reactions proceeded in similar yields to the those reported for comparable solution‐state reactions ( 4 a (22 %), vs. 20–50 % in solution [28a,c] ) and carbazole ( 4 b (36 %) vs. 42–43 % in solution [28a,c] ). Electron rich groups were readily tolerated, for example para ‐methoxy substituted diphenyl amine gave 4 c in 44 % yield (cf.…”
Section: Resultssupporting
confidence: 77%
See 2 more Smart Citations
“…The scope of the reaction was assessed (Scheme 3) using a range of diaryl and aryl/alkyl secondary amines to yield 4 a – 4 d in the solid state (Figure 5). These reactions proceeded in similar yields to the those reported for comparable solution‐state reactions ( 4 a (22 %), vs. 20–50 % in solution [28a,c] ) and carbazole ( 4 b (36 %) vs. 42–43 % in solution [28a,c] ). Electron rich groups were readily tolerated, for example para ‐methoxy substituted diphenyl amine gave 4 c in 44 % yield (cf.…”
Section: Resultssupporting
confidence: 77%
“…These conditions gave an excellent isolated yield for the phenyl substituted c‐NDI after 60 min reaction time ( 2 b , 83 %). This may be compared to reported solution‐state synthetic routes to phenyl substituted c‐NDIs (10 %; Suzuki coupling, 14 h, 100 °C, under nitrogen) [28c,33] and 80 % (CH arylation, 72 h, benzene under reflux) [34] …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[3][4][5][6]59,64 Any compounds with closely-lying 1 CT, 3 CT and 3 LE states may exhibit TADF properties (or more generally, close-lying S 1 /T 1 states). 65,66 Recently, we prepared a compact, orthogonal electron donor-acceptor dyad, with naphthalimide (NI) as the electron acceptor and phenothiazine (PTZ) as the electron donor (Fig. 6).…”
Section: Observation Of Localized Triplet States: Different Isc Mecha...mentioning
confidence: 99%
“…We have previously studied intramolecular triplet energy transfer in Bodipy dimers exhibiting SOCT-ISC , and intermediate triplet states in a thermally activated delayed fluorescence (TADF) material. , It has been shown that reversible intramolecular processes, including energy transfer between the two subunits in the dimer, change the electron spin polarization (ESP) of the observed states and the shape of the spectrum and increase the anisotropic spin–lattice relaxation. , These properties enable us to describe the processes that occur during photoexcitation of dimers and to establish the presence of dynamic equilibrium between the excited states of the two monomers. To further study these phenomena, we have prepared two new dimers (Scheme ).…”
Section: Introductionmentioning
confidence: 99%